Role of carboxypeptidases to the free amino acid composition, methylpyrazine formation and sensory characteristic of under- fermented cocoa beans - Selamat, Jinap; Lioe, Hanifah Nuryani; Yusep, I.; Saari, Nazamid; Bakar, Jamilah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
The role of carboxypeptidases B (from porcine) and Y (from baker's yeast), applied to under-fermented cocoa beans, on the formation of cocoa-specific aroma precursors, the aroma and sensory quality after roasting was investigated. The application of carboxypeptidases in under-fermented cocoa beans was to overcome the slaty and purple beans with an excessive taste of their bitterness and astringency after roasting, and the lack of cocoa-specific aroma attribute. The 5% carboxypeptidases B and Y were applied separately on the dry-powdered under-fermented cocoa beans at several incubation periods (6, 12, 24, 48 h). The levels of free amino acids, especially hydrophobic amino acids as essential cocoa aroma precursors, were significantly higher in cocoa beans treated with carboxypeptidase B as compared to the control. This led to the higher levels of 2,5-dimethyl-, 2,3,5-trimethyl- and 2,3,5,6-tetramethylpyrazines found in the samples after roasting at 150°C for 15 min. Therefore, carboxypeptidase B was more efficient for the formation of the cocoa-specific aroma compared to carboxypeptidase Y. However, both carboxypeptidase treatments had no significant effect (p>0.05) on flavor attributes of cocoa liquors made from the roasted cocoa beans, eventhough there is a significant correlation between the formation of hydrophobic free amino acids with cocoa-specific flavor attribute and between the methylpyrazines with the flavor attribute (r2 = 0.91 - 0.99).